Pulmonary hypertension registry of Kerala, India (PRO-KERALA) — Clinical characteristics and practice patterns. (15th August 2018) - Harikrishnan, S.; Sanjay, G.; Ashishkumar, M.; Menon, Jaideep; Rajesh, Gopalan Nair; Kumar, Raman Krishna; George Koshy, A.; Attacheril, Thankachan V.; George, Raju; Punnoose, Eapen; Ashraf, S.M.; Arun, S.R.; et al.
Abstract: Background: Epidemiological data on pulmonary hypertension (PH) are scarce from developing countries including India. Methods: We established a multi-center registry of PH, the PRO-KERALA registry, in Kerala, India. Fifty hospitals enrolled consecutive adult (>18 years) patients for one year. Echocardiographic criteria (right ventricular systolic pressure – RVSP > 50 mmHg) or invasively obtained mean pulmonary artery pressure > 25 mmHg was the criteria for entry. Results: There were 2003 patients (52% Women, mean age 56 ± 16.1 years) enrolled. The mean RVSP was 68.2 (SD = 17.9) mmHg. Majority of the study participants (59%) belonged to group 2 of the WHO Nice Classification 2013 (PH secondary to left heart disease). One-fifth (21.2%) belonged to group 1, while 13.3%, 3.8% and 2.4% of the study population belonged to groups 3, 4 and 5 respectively. More than a quarter (27%) reported PH due to left heart disease with valvular disease etiology; while 20.7% had coronary artery disease. The other common etiological factors were chronic obstructive pulmonary disease (10.6%), congenital heart disease (14.6%), idiopathic pulmonary hypertension (5.8%), and chronic thromboembolic pulmonary hypertension (3.8%). Only one of two patients with pulmonary artery hypertension was receiving PH specific therapies. The use of combination therapy was negligible and PH-specific therapies were prescribed off-label to a small proportion of patients too. Conclusion: PRO-KERALA is the first PH registry from South Asia and the second largest globally. Left heart diseases attribute to three fifths of patients with PH. Utilization rates of PH specific drug therapies are remarkably lower than the Western population. Graphical abstract: PROKERALA registry with 2003 pulmonary hypertension (PH) patients is the largest reported registry from India and the low and middle-income region. The chart above shows the proportion of patients (%) in different categories of PH and their mean age. Left heart diseases attributed to three fifths of patients with PH, of them 27% and 21% were due to valvular heart disease and coronary artery disease, respectively.